Culture, Female Labour Force Participation, and Selective Migrationː New Meta-Analytic Evidence - Eva Markowsky (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2022)
I analyse about 160 estimates of the relationship between female migrants' labour force participation and ancestry culture, integrating studies from economics and sociology that were previously unconnected. The literature exhibits large heterogeneity in results that is only partly explained by differences in data, sample selection, and methods. Part of the excess heterogeneity seems to be driven by selective reporting with preference given to studies that ftnd positive and statistically significant correlations between ancestry culture and female labour force participation. Differential composition of countries of ancestry proves another important source of heterogeneity. Estimations drawn from data with higher average ancestry-gender equality ftnd lager culture effects, implying that the behaviour of women from low-gender equality countries might not be representative for their country of origing culture. I discuss how cultural selection of immigration could explain this relationship and why it can bias measured culture effects. The analysis provides valuable insights for future applications of the socio-epidemiological approach.
Keywords: 330; Weibliche Arbeitskräfte; Migranten; Kulturelle Identität; Korrelation; Welt